ANALISIS PENGARUH DIMENSI KUALITAS PELAYAN JASA RUMAH SAKIT SELASIH TERHADAP KEPUASAN PASIEN (Jurnal Pelangi : Research of Education and Development, 2011)
This research is intended to measure hospitalized patients' satisfaction toward dimension ofSelasih Hospital service quality. It covers realibility, reponsiveness, assurance, emphaty, andtangibility. The researcher used close questions in collecting the primary data. She collected thedata by using non probability sampling through convenience sampling. There were 170 patientstaken as samples, they were divided into three classes; I, II and III. The used method of analysisis; multiple linier regression . The multiple linier regresion analysis on service quality variablewhich covers reability dimension, responsiveness, assurance, emphaty and tangibility hasresulted in positive and significance influence on hospitalized patients’ satisfaction.